The Effect of Soy Milk on Increasing Hemoglobin (Hb) Levels in Pregnant Women - Rohmah, Hajar Nur Fathur (Universitas Islam Lamongan, 2023)
Anemia is a condition in which hemoglobin (Hb) levels in the blood are below normal. However, the compliance of pregnant women with the consumption of iron tablets for 90 days is very low at 38%, citing unpleasant side effects (UNICEF, 2019). Alternative food sources that contain high iron are dates and soybeans. Date palm fruit contains carbohydrates, fiber, calcium, vitamins, potassium, iron which serves to replace lost energy. Based on a preliminary survey conducted by researchers in Bantarjaya Village by conducting hemoglobin tests on 5 pregnant women, it was found that 3 pregnant women had anemia and 2 pregnant woman was not anemic. The purpose of this study was to determine the effect of giving date soy milk on increasing hemoglobin (HB) levels in pregnant women in Bantarjaya Village, Bekasi Regency in 2023. The research method was carried out using quantitative research methods with a Quasi-Experimental approach using Wilcoxon statistical tests (Abnormally Distributed). The population in this study was all pregnant women in Bantarjaya Village which was 29 people. The sample in this study was pregnant women in Bantarjaya Village using total sampling technique. Data collection by questionnaire. Data analysis is univariate and bivariate analysis. The results showed that of 29 pregnant women, HB levels during the pretest, the most in mothers who were not anemic, which was 62.1% compared to mothers who had anemia 37.9%. After being given date soy milk (post test), mothers who experienced no anemia increased to 29 people (100%). Meanwhile, mothers who had anemia reduced to 0%. The results of statistical tests are known to Asymp. Sig is 0.000 (P < 0.05), hence it can be concluded that the hypothesis is accepted. This means that there is a difference between the Pretest and Posttest results, so it can also be concluded that there is an influence on the provision of date soy milk on increasing HB levels in pregnant women in Bantarjaya Village, Pebayuran District, Bekasi Regency in 2023. There needs to be a role from health workers, health cadres, local village leaders and the Health Office to increase the knowledge of pregnant women, especially about anemia and how to prevent it.